Remote sensing of forest gas exchange: Considerations derived from a tomographic perspective. (8th February 2020) - Damm, Alexander; Paul‐Limoges, Eugenie; Kükenbrink, Daniel; Bachofen, Christoph; Morsdorf, Felix
Abstract: The global exchange of gas (CO2, H2 O) and energy (sensible and latent heat) between forest ecosystems and the atmosphere is often assessed using remote sensing (RS) products. Although these products are essential in quantifying the spatial variability of forest–atmosphere exchanges, large uncertainties remain from a measurement bias towards top of canopy fluxes since optical RS data are not sensitive for the vertically integrated forest canopy. We hypothesize that a tomographic perspective opens new pathways to advance upscaling gas exchange processes from leaf to forest stands and larger scales. We suggest a 3D modelling environment comprising principles of ecohydrology and radiative transfer modelling with measurements of micrometeorological variables, leaf optical properties and forest structure, and assess 3D fields of net CO2 assimilation ( A n ) and transpiration ( T ) in a Swiss temperate forest canopy. 3D simulations were used to quantify uncertainties in gas exchange estimates inherent to RS approaches and model assumptions (i.e. a big‐leaf approximation in modelling approaches). Our results reveal substantial 3D heterogeneity of forest gas exchange with top of canopy A n and T being reduced by up to 98% at the bottom of the canopy. We show that a simplified use of RS causes uncertainties in estimated vertical gas exchange of up to 300% and that the spatial variation of gas exchange in the footprint of flux towers can exceed diurnal dynamics. We also demonstrate that big‐leaf assumptions can cause uncertainties up to a factor of 10 for estimates of A n and T . Concluding, we acknowledge the large potential of 3D assessments of gas exchange to unravelling the role of vertical variability and canopy structure in regulating forest–atmosphere gas and energy exchange. Such information allows to systematically link canopy with global scale controls on forest functioning and eventually enables advanced understanding of forest responses to environmental change. Abstract : We suggest a 3D modelling environment to simulate 3D fields of net CO2 assimilation and transpiration in forest canopies. We demonstrate the capability of the resulting tomographic perspective to investigate diurnal 3D dynamics of forest gas exchange, to unravel possible uncertainties in remote‐sensing‐based estimates of forest gas exchange, and to quantify uncertainties associated with simplifications of complex canopies in modelling approaches. The suggested tomographic perspective on forest gas exchange shall stimulate research on possible linkages between leaf‐ and ecosystem‐level processes with explicit account for complex 3D heterogeneities.